Situational Judgement Tests among Palestinian community members and Red Crescent volunteers to inform humanitarian action: a cross-sectional study - L. S. Moussaoui; M. Quimby; H. Avancini; A. Salawdi; F. Skaik; R. Bani Odeh; O. Desrichard; N. Claxton (BMC, 2024)
Abstract Background Informing humanitarian action directly from community members is recognized as critical. However, collecting community insights is also a challenge in practice. This paper reports data collected among community members and Red Crescent volunteers in the occupied Palestinian territory. The aim was to test a data collection tool, situational judgment tests (SJTs), to collect insights in the community around three themes. Methods The SJTs covered violence prevention, road safety, and environmental pollution (waste), and were constituted of hypothetical scenarios to which respondents indicated how they would react. For each theme, the answers' pattern provides insights for humanitarian action regarding which beliefs to address. A cross-sectional survey was conducted in January and February 2023 with 656 community members, and 239 Red Crescent volunteers. Results Data showed that violence is the theme for which the need is the highest among community members. Some responses varied according to the public (age, governorate, or disability level), suggesting actions could be tailored accordingly. Conclusions Despite many difficulties during data collection, this study show that the tool allowed to collect community insights, a crucial task to ensure adequate response to the challenges faced by community members and Red Crescent volunteers in occupied Palestine.